In singing, he composed a song - Stewart, Jeremy, 1982- (Brave & brilliant series, 2021)
"John Stevenson is late for his high school Alternate Education class because he has been at the Health Unit undergoing testing for STDs. When he finally shows up, a series of apparently minor coincidences set the stage for a confrontation with the RCMP that leaves John battered and without cigarettes in a Seclusion Room at the Prince George Regional Hospital. Here, John has time to think about the long arc of violence and drugs that brought him to this point--and the future it seems he can only destroy. The story is told through an assemblage of texts, voices, and fragments that include prose, lined poetry, photography, a transcribed interview, an epistle, psychiatric records, literary theory essay fragments, and more."--